Kano, Koichi, ed. 2022. An Invitation to Chaucer’s Cosmos. チョーサー巡礼:古典の遺産と中世の新しい息吹きに導かれて. Tokyo: Yushokan. Pp. xvi + 548. ISBN 9784865820478. - Yoshinobu Kudo (SELIM)
Book review of Kano, Koichi, ed. 2022. An Invitation to Chaucer’s Cosmos. チョーサー巡礼:古典の遺産と中世の新しい息吹きに導かれて. Tokyo: Yushokan. Pp. xvi + 548. ISBN 9784865820478.